Controlled diffeomorphic extension of homeomorphisms. (December 2018) - Koskela, Pekka; Wang, Zhuang; Xu, Haiqing
Abstract: Let Ω be an internal chord-arc Jordan domain and φ : S → ∂ Ω be a homeomorphism. We show that φ has finite dyadic energy if and only if φ has a diffeomorphic extension h : D → Ω which has finite energy.